Graphene oxide nanocomposites based room temperature gas sensors: A review - Thangamani, G J; Deshmukh, Kalim; Kovářík, Tomáš; Nambiraj, N A; Ponnamma, Deepalekshmi; Sadasivuni, Kishor Kumar; Khalil, H P S Abdul; Pasha, S K Khadheer (Chemosphere, 2021)
Over the last few decades, various volatile organic compounds (VOCs) have been widely used in the processing of building materials and this practice adversely affected the environment i.e. both indoor and outdoor air quality. A cost-effective solution for detecting a wide range of VOCs by sensing approaches includes chemiresistive, optical and electrochemical techniques. Room temperature (RT) chemiresistive gas sensors are next-generation technologies desirable for self-powered or battery-powered instruments utilized in monitoring emissions that are associated with indoor/outdoor air pollution and industrial processes. In this review, a state-of-the-art overview of chemiresistive gas sensors is provided based on their attractive analytical characteristics such as high sensitivity, selectivity, reproducibility, rapid assay time and low fabrication cost. The review mainly discusses the recent advancement and advantages of graphene oxide (GO) nanocomposites-based chemiresistive gas sensors and various factors affecting their sensing performance at RT. Besides, the sensing mechanisms of GO nanocomposites-based chemiresistive gas sensors derived using metals, transition metal oxides (TMOs) and polymers were discussed. Finally, the challenges and future perspectives of GO nanocomposites-based RT chemiresistive gas sensors are addressed.
Keywords: grafit; GO based nanocomposites; Reproducibility of Results; nanokompozity; VOCs sensors; RT gas sensors; Temperature; reprodukovatelnost výsledků; Nanocomposites; Graphite; teplota